Shari’ah supervisory board’s size impact on performance in the Islamic banking industry: empirical investigation of the optimal board size across jurisdictions - Haron, Razali; Nomran, Naji (Emerald Publishing Limited, 2020)
Abstract Purpose – This study aims to empirically examine whether there is any optimal Shari’ah supervisory board’s (SSB) size that maximizes performance of Islamic banks (IBs). Apparently, IBs adopt different SSB size based on their different regulations across jurisdictions, and then it is still questionable whether there is any optimal SSB size that can fit all and be recommended to IBs. Design/methodology/approach – The paper investigates the impact of different SSB size on IBs performance using a sample of 113 banks over 23 countries for the period 2007-2015 based on the generalized method of moments estimator. Findings – The empirical evidence documented in this study strongly highlights the importance of small SSB size in enhancing the performance of IBs as compared to the large board size. The findings confirm that the SSB size of IBs should neither be lesser than three nor greater than six. More specifically, it is found that the optimal SSB size seems to be five. Research limitations/implications – First, the study does not investigate whether the findings are constant during crisis and non-crisis periods. Second, the optimal SSB size in IBs should be confirmed from the risk-taking perspective besides performance. Practical implications – For both the IBs and the regulators, they should give due importance to small SSB size as an important element for improving the IBs performance. It is strongly recommended for the IBs to have a SSB size between three and six, and five is the most recommended. The Accounting and Auditing Organization for Islamic Financial Institutions also should revise their existing standards that only suggest the minimumSSB size of three to include the maximum size of six and the optimal size of five. Originality/value – Despite the SSB size plays an important role in affecting the performance of IBs, it seems there are no empirical studies attempting to address whether there is any optimal SSB size that can enhance the IBs performance so far. Keywords Performance, Islamic banks, Shari’ah governance, Shari’ah supervisory board, Optimal board size Paper type Research paper